PENGARUH KECERDASAN AKUNTANSI TERHADAP PEMAHAMAN PELAJARAN AKUNTANSI - Bella Agustina; Noor Shodiq Askandar (e_Jurnal Ilmiah Riset Akuntansi, 2018)
ABSTRACTThe success of student life is not only influenced by intellectualintelligence (IQ), but also influenced by other intelligence, namely emotionalintelligence (EQ). The purpose of this study was to determine whether emotionalintelligence affects the level of understanding of accounting. Emotionalintelligence is measured from self-recognition, self-control, motivation, empathy,and social skills, while the level of understanding of accounting. The populationin this study were 95 students of accounting at SMKN 1 Malang. Populationsampling was 93. Data were obtained through a questionnaire method with aLikert scale, which was adopted from the Salovey-Mayer Defining sample usingthe Solvin method, while the analysis used multiple linear analysis methods. Theindependent variables in this study are self-recognition, self-control, motivation,empathy, and social skills; while the dependent variable is the level of students'accounting understanding. Data obtained with the help of SPSS 13. softwareBased on the results, of the five hypotheses presented, hypotheses 1, 2, and 3 wereaccepted which stated that self-recognition, self-control, motivation had an effecton students' level of accounting understanding. Whereas hypotheses 4 and 5 arerejected which state that empathy and social skills do not affect the level ofunderstanding of accounting. Many emotional intelligence factors are influentialin individual life, in this case students. For example mental stress factors, socialenvironment, failure trauma, personal problems, activities outside campus (work),culture, or it could be caused by student learning behavior. Keywords: EmotionalIntelligence (EQ), Accounting Understanding Level (GPA), self-recognition, selfcontrol, motivation, empathy, and social skills.Keywords : emotional intelligence, level of understanding of accounting, selfrecognition, self-control, motivation, empathy, and social skills